2019
DOI: 10.1111/jvh.13235
|View full text |Cite
|
Sign up to set email alerts
|

Vibration‐controlled transient elastography for the detection of cirrhosis in chronic hepatitis D infection

Abstract: Noninvasive detection of cirrhosis via vibration‐controlled transient elastography (VCTE) has revolutionized the management of chronic hepatitis B virus (HBV) and hepatitis C virus (HCV) infection. However, VCTE has not been studied in chronic hepatitis D virus (HDV) infection and accuracy remains in question due to the significant hepatic inflammation associated with this infection. Consecutive HBV, HCV and HDV patients who underwent VCTE (2006‐2019) were evaluated. Diagnosis of cirrhosis was made via liver b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 55 publications
6
39
1
1
Order By: Relevance
“…We based the diagnosis of liver cirrhosis on laboratory values (e.g. platelets below 150/nl, albumin <35 g/L, INR >1.25), transient elastography (Fibroscan®) examination with a cut‐off of ≥12.5 kPa 6 and ultrasonography of the liver. Following ultrasound features were considered as indicative for cirrhosis: the presence of collaterals or ascites, liver nodularity, right lobe atrophy, hypertrophy of the left lobe or caudate lobe, liver surface irregularities in high‐resolution ultrasound and splenomegaly.…”
Section: Methodsmentioning
confidence: 99%
“…We based the diagnosis of liver cirrhosis on laboratory values (e.g. platelets below 150/nl, albumin <35 g/L, INR >1.25), transient elastography (Fibroscan®) examination with a cut‐off of ≥12.5 kPa 6 and ultrasonography of the liver. Following ultrasound features were considered as indicative for cirrhosis: the presence of collaterals or ascites, liver nodularity, right lobe atrophy, hypertrophy of the left lobe or caudate lobe, liver surface irregularities in high‐resolution ultrasound and splenomegaly.…”
Section: Methodsmentioning
confidence: 99%
“…In patients with a positive anti-HDV, irrespective of viral load, assessment of liver disease staging should be undertaken using locally available noninvasive, or where required, invasive (liver biopsy) tools. Noninvasive liver staging tools used in the setting of HDV include the aspartate aminotransferase (AST) to platelet ratio index (APRI) and the fibrosis-4 score (FIB4), as well as measures of liver stiffness with transient elastography [36,37]. If HDV RNA is negative, ongoing monitoring is required with view to repeat testing as clinically indicated.…”
Section: Treatmentmentioning
confidence: 99%
“…In 2020, the first antiviral agent for hepatitis D was approved under conditional authorization by the European Medical Agency for patients with compensated liver disease and positive viraemia with or without nucleos(t)ide analogueshere [36,42]. Bulevirtide (Hepcludex ® ) 2 mg subcutaneous daily stops HDV and HBV from entering the human hepatocyte allowing for recovery, protecting uninfected cells and allowing potential clearance.…”
Section: Treatmentmentioning
confidence: 99%
“…However, the high cost, patient acceptability, sampling error, inter-observer, intra-observer variability, and the risk of complications such as bleeding and infection have limited its widespread clinical application [8] . Numerous recent studies have shown that transient elastography (TE), serum biochemical tests, and Mac-2 binding protein glycosylation isomer (M2BPGi) are promising non-invasive tools for the diagnosis of liver brosis in LT recipients and patients with chronic Hepatitis B (CHB) [9][10][11][12][13] . However, none of the above methods could thoroughly assess liver brosis, and clinicians cannot make a holistic judgment of the distribution and development of liver brosis.…”
Section: Introductionmentioning
confidence: 99%